Relationship Between Learning Strategies and Students' Learning Outcomes at Taqwa Pandam TPA - Nada Etana; Vevi Sunarti (Universitas Negeri Padang, 2021)
This research is motivated by learning strategies that affect student learning outcomes at TPA Taqwa Pandam, Bonjol District, Pasaman Regency. This study aims to determine the application of learning strategies that affect student learning outcomes. This type of research is quantitative descriptive and correlational. The population of this research is 50 students at TPA Taqwa Pandam, Bonjol District, Pasaman Regency. The sampling technique used is class random sampling technique. The sample taken is 45% of the existing population as many as 22 people. The data collection technique used is a questionnaire, the data collection tool uses a questionnaire containing a list of statements. The data analysis technique in this study used percentages and Spearman Rho. The results of this study indicate that (1) the learning strategies applied in learning the Qur'an at TPA Taqwa Pandam, Bonjol District, Pasaman Regency is classified as low, (2) the learning outcomes of students are low, most of the students have not reached the Minimum Completeness Criteria (KKM) or have not been completed, (3) There is a significant relationship between learning strategies and student learning outcomes at TPA Taqwa Pandam, Bonjol District, Pasaman Regency.Keywords: Learning Strategies, Learning Outcomes, Students.